Integer Programming for Optimal Control of Geostationary Station Keeping of Low-Thrust Satellites. Issue 1 (July 2017) - Gazzino, C.; Louembet, C.; Arzelier, D.; Jozefowiez, N.; Losa, D.; Pittet, C.; Cerri, L.
Abstract: A control scheme is elaborated to perform the station keeping of a geostationary satellite equipped with electric propulsion. The use of electric thrusters imposes to take into account some additional mutually exclusive constraints on the control function that can be reformulated as logical constraints. The resulting fuel optimal station keeping problem is thus not solved with classical methods, either direct or indirect, but is transformed into a linear integer programming problem. The linearised relative velocity of the satellite is computed and some linear constraints on this velocity are added to the original station keeping problem in order to perform the station kepping over one week after another. Simulation results validate the efficiency of the optimal control thrusts obtained by the solution of the overall linear integer programming problem.